2015
DOI: 10.1007/s11748-015-0521-3
|View full text |Cite
|
Sign up to set email alerts
|

Kommerell’s diverticulum in the current era: a comprehensive review

Abstract: Kommerell's diverticulum is a developmental error with a remnant of fourth dorsal aortic arch, named after Dr. Kommerell, a radiologist, who made the first diagnosis in a living individual. The diverticulum can occur in both the left and right aortic arch, from which an aberrant subclavian artery rises to the contralateral side. Pediatric patients often present with airway symptoms whereas dysphagia and chest discomfort are more common in the adult patients. Computed tomography or magnetic resonance imaging ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
202
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(217 citation statements)
references
References 138 publications
2
202
0
13
Order By: Relevance
“…4) Tanaka et al reported that the mean Kommerell diverticulum diameter was 4.6 cm ± 1.3 cm when the rupture occurred and 4.6 cm ± 2.0 cm when dissection was performed. 8) In the present case, we judged that surgery was indicated, given the acute type A aortic dissection with ULP and the large Kommerell diverticulum.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…4) Tanaka et al reported that the mean Kommerell diverticulum diameter was 4.6 cm ± 1.3 cm when the rupture occurred and 4.6 cm ± 2.0 cm when dissection was performed. 8) In the present case, we judged that surgery was indicated, given the acute type A aortic dissection with ULP and the large Kommerell diverticulum.…”
Section: Discussionmentioning
confidence: 78%
“…6) Tanaka et al reported that the early operative mortality associated with surgery for Kommerell diverticulum was 11% and that the causes of death included acute pulmonary embolism, multiple organ failure, sepsis, and hemorrhage. 8) Although postoperative outcomes are improving, one-stage, widerange open-graft replacement remains unsafe.…”
Section: Discussionmentioning
confidence: 99%
“…Nos adultos, vem sendo associado à cirurgia o procedimento endovascular (híbrido) 18 . A complicação operatória mais frequente é o quilotórax, recomendando-se sempre a dissecção próxima ao divertículo (19) . Outras complicações no pós-operatório são a persistência dos sintomas respiratórios, frequentemente decorrentes da traqueomalácea, da estenose traqueal ou de lesões do parênquima pulmonar.…”
Section: Discussionunclassified
“…the Kommerell's diverticulum in the broad sense), and (3) aortic diverticulum at the level of aorto-ductal junction, ductus diverticulum (this category is not considered as Kommerel's diverticulum). There are reports of the ''Kommerell's diverticulum'' without aberrant subclavian artery, but it seems reasonable to categorize this kind of dilation into the third type [7,8]. The presence of a right subclavian artery aneurysm in an adolescent with a BAV has been recently reported [9].…”
Section: Introductionmentioning
confidence: 99%